The Mouse Superior Colliculus: An Emerging Model for Studying Circuit Formation and Function - Ito, Shinya; Feldheim, David A. (Frontiers in Neural Circuits, 2018)
The superior colliculus (SC) is a midbrain area where visual, auditory, and somatosensory information are integrated to initiate motor commands. The SC plays a central role in visual information processing in the mouse; it receives projections from 85–90% of the retinal ganglion cells (RGCs). While the mouse SC has been a long-standing model used to study retinotopic map formation, a number of technological advances in mouse molecular genetic techniques, large-scale physiological recordings, and SC-dependent visual behavioral assays have made the mouse an even more ideal model to understand the relationship between circuitry and behavior.